Avaliação da fragilidade mandibular ao trauma devido à presença de terceiros molares : uma análise tridimensional com elementos finitos - Bezerra, Tácio Pinheiro (2012)
The mandibular angle has been described as fragile area, the presence of the third molar has been suggested to contribute to increased mandibular fragility because the mandible loses parts of its bone structure to harbor an organ that does not contribute to its strength. In this context, the article produced on this thesis had the objective of identify areas of tension concentration and its distribution on the mandibular angle if both third molar were present, if only one was present, and without third molars. Each mandible was submitted to blunt mentual trauma and evaluated by a finite element methodology. A mandible was reconstructed through the discretization of masks by a digital process of identification of structures considering the tomographic density to the cortical and medullar bone, periodontal ligament, cement, dentin, enamel and pulp. To differentiate the structures, the first mandible with both third molars was submitted to a digital replacement of the mask from the third molar structures to the masks of the cortical and medullar bone. Therefore, producing the two other structures of the study. To reproduce the normal anatomic situation, the external nodes of the most posterior and superior part of the mandibular condyle were fixated in all degrees of freedom bilaterally, and elements were created to reproduce the actions of the masticatory muscles. Each structure was submitted to a blunt mentual trauma, perpendicularly to the frontal plane, with 250 kilograms of magnitude. The results were evaluated by the description of the chromatic stress distribution diagram of Von Misses. A highly detailed, patient-specific, custom-made, high-resolution model of the mandible could be generated with a very dense volume mesh (914.952 elements for the mandible 01, 867.183 for 02, and 831.897 for 03). Due to the detailed method of body prove attainment and to the study methodology it was possible to obtain adequate results to the dynamic of the impact. According to the diagram of the dispersion of tensions, whenever the third molar was present, unilateral or bilateral, there was a greater concentration of tensions around the cervical part of the alveolus. However, when absent the stress concentration was more significant on the condylar neck. The present study showed an experimental model that reproduces the mandibular dynamics and the behavior of the mandibular structure to a mentual trauma. As a conclusion, the third molar is responsible to a tension concentration on the region of the external oblique ridge and retromolar area justifying that these teeth contribute to the mandibular angle fragility.